Can we replace exercises targeted on core/hip muscles by exercises targeted on leg/foot muscles in women with patellofemoral pain? A randomized controlled trial. (November 2022) - Pompeo, Klauber Dalcero; da Rocha, Emmanuel Souza; Melo, Mirella Ayres; de Oliveira, Nathalia Trevisol; Oliveira, Daniel Fernandes; Sonda, Francesca Chaida; dos Santos, Patrícia Freitas; Rodrigues, Rodrigo; Baroni, Bruno M.; Vaz, Marco A.
Abstract: Objective: To verify the effects of replacing exercises targeted on core/hip muscles by exercises targeted on leg/foot muscles in a rehabilitation program for patellofemoral pain (PFP). Design: Randomized Controlled Trial. Participants: Fifty women with PFP. Methods: PFP participants were randomized into the standard rehabilitation group (SRG, n = 25) or distal exercise group (DEG, n = 25). Knee pain, patient-reported function, dynamic knee valgus and muscle strength were measured at baseline and after six and twelve weeks of the program start. Results: SRG and DEG presented similar responses to rehabilitation (except for muscle strengthening). Knee pain reduced after 6 weeks (SRG: −37.7%, ES = 1.23; DEG: −30%, ES = 0.93) and 12 weeks (SRG: −47.4%, ES = 1.53; DEG: −43.3%, ES = 1.46). Patient-reported function improved after 6 weeks (SRG: +7.3%, ES = 0.45; DEG: +3.8%, ES = 0.22) and 12 weeks (SRG: +14.1%, ES = 0.80; DEG: +8.8%, ES = 0.50). Dynamic knee valgus reduced after 12 weeks (SRG: −29.7%, ES = 0.38; DEG: −34.5%, ES = 0.32). Both groups experienced increases in knee extension strength (SRG: +9%, ES = 0.28; DEG: +6%, ES = −0.29), but only SRG had strength gains for hip abduction (+10%, ES = 0.36) and extension (+11%, ES = 0.44). Conclusion: Exercises targeted on core/hip muscles can be replaced by exercises targeted on leg/foot muscles in a lower limb exercise-based rehabilitation program for women with PFP. Clinical trial registration: NCT03663595. Highlights: Clinicians can target core/hip muscles or leg/foot muscles in PFP rehabilitation. 6 weeks of rehabilitation increased functionality and reduced pain in PFP women. Hip muscles strength increased only with exercises targeted on core/hip muscles.